A tapered diffusion impact indicator: A preliminary exploration on the journal level - Lin, Zhang (Malaysian Journal of Library and Information Science, 2017)
We introduce an indicator (DT) to measure the diffusion impact of scientific research. The indicator focuses on the variety of citing sources by giving a full credit when a new citing source makes an appearance, and a tapered credit when a new citing paper appears in an already used existed source. As a preliminary study, we only used a simple example with individual journals as the diffusion units. A sample from a highly interdisciplinary journal, Chemometrics and Intelligent Laboratory Systems, is used to illustrate this procedure. From the theoretical analysis and experimental examples, the DT index proved an efficient function for differentiating the scope of citation diffusion